Continuous delivery of naltrexone and nalmefene leads to tolerance in reducing alcohol drinking and to supersensitivity of brain opioid receptors. (15th March 2016) - Korpi, Esa R.; Linden, Anni‐Maija; Hytönen, Heidi R.; Paasikoski, Nelli; Vashchinkina, Elena; Dudek, Mateusz; Herr, Deron R.; Hyytiä, Petri
Abstract: Opioid antagonist treatments reduce alcohol drinking in rodent models and in alcohol‐dependent patients, with variable efficacy across different studies. These treatments may suffer from the development of tolerance and opioid receptor supersensitivity, as suggested by preclinical models showing activation of these processes during and after subchronic high‐dose administration of the short‐acting opioid antagonist naloxone. In the present study, we compared equipotent low and moderate daily doses of naltrexone and nalmefene, two opioid antagonists in the clinical practice for treatment of alcoholism. The antagonists were given here subcutaneously for 7 days either as daily injections or continuous osmotic minipump‐driven infusions to alcohol‐preferring AA rats having trained to drink 10% alcohol in a limited access protocol. One day after stopping the antagonist treatment, [ 35 S]GTPγS autoradiography on brain cryostat sections was carried out to examine the coupling of receptors to G protein activation. The results prove the efficacy of repeated injections over infused opioid antagonists in reducing alcohol drinking. Tolerance to the reducing effect on alcohol drinking and to the enhancement of G protein coupling to μ‐opioid receptors in various brain regions were consistently detected only after infused antagonists. Supersensitivity of κ‐opioid receptors was seen in the ventral and dorsal striatal regions especially by infused nalmefene. Nalmefene showed no clear agonistic activity in rat brain sections or at human recombinant κ‐opioid receptors. The findings support the as‐needed dosing practice, rather than the standard continual dosing, in the treatment of alcoholism with opioid receptor antagonists. Abstract : Opioid receptor antagonists naltrexone and nalmefene reduced alcohol drinking of alcohol‐preferring AA rats without tolerance when given as daily injections but not when the same doses were given as continuous delivery via osmotic minipumps. After 1 week of treatment, μ‐opioid (and to lesser extent also κ‐opioid) receptor supersensitivity was seen in many brain regions after continuous delivery, but not after injections. The results support as‐needed dosing of the opioid antagonists in the treatment of alcoholism.